Land tenure, migration, and development: a comparative case study - Garni, Alisa M. (My University, 2013)
Comparative analysis of two Salvadoran towns with similar patterns of international migration but different historical land-tenure patterns reveals the emergence of radically different development strategies. Whereas in one case, mostly landed households with a history of farming commercially have been selling land and abandoning agriculture, in the other case, previously landless households whose members worked as sharecroppers before the onset of migration have been acquiring land and farming as much as possible. The opposite processes at work in these two cases raise important theoretical questions for both migration and development studies. Using ethnographic, census, and historical data, I examine how and why land ownership, under particular historical circumstances, conditions the impact of migration on development.
Keywords: Land tenure; Migration; Land ownership; Development